Evolution of Sea Surface Hydrology Along the Western Australian Margin Over the Past 450 kyr. Issue 11 (5th November 2021) - Pei, Renjie; Kuhnt, Wolfgang; Holbourn, Ann; Jöhnck, Janika; Hingst, Johanna; Beil, Sebastian; Lübbers, Julia; Andersen, Nils
Abstract: We collected a suite of core top samples during R/V Sonne Cruise SO257 in May 2017 along the southwestern front of the Indo‐Pacific Warm Pool (IPWP) to monitor the variability of Southern Hemisphere tropical and subtropical sea surface hydrology and to assess temperature and salinity reconstructions with data sets reflecting conditions in the post‐monsoonal season. In our core top samples, a steep increase in planktic δ 18 O, associated with a decrease in sea surface temperature (SST), indicates that the southwestern front of the IPWP is located between 23° and 24°S during austral fall. We additionally reconstructed SST, sea surface salinity, and δ 18 O seawater (δ 18 Osw ) over the last 450 kyr in two sediment successions located within and beyond the monsoonal rain belt. Our records show that SST was highly coherent and phase‐locked with atmospheric p CO2 during the last 450 kyr. The regional differences in the δ 18 Osw records reveal that the Western Australian Margin north of 15°S remained seasonally under the influence of IPWP water masses, even during glacials. The temporal variability in upper ocean hydrology along the Western Australian Margin is not directly coupled to local monsoonal precipitation, but is strongly affected by advective mixing of Indonesian Throughflow derived water masses. Key Points: Southwest front of modern Indo‐Pacific Warm Pool (IPWP) during austral fall is located between 23° and 24°S Western Australian Margin north of 15°S remained seasonally influenced by IPWP throughout past 450 kyr Upper ocean hydrology off Western Australia represents an integrated signal of monsoonal precipitation and advective mixing